Regulatory roles of androgens in cutaneous wound healing - Gilliver, Stephen C.; Wu, Fred; Ashcroft, Gillian S. (Thrombosis and Haemostasis, 2003)
Although the effects of androgens on wound healing are poorly characterised, the androgen receptor is expressed by inflammatory cells, keratinocytes and fibroblasts during wound healing, suggesting that androgens may regulate inflammatory and/or repair processes. In fact, it appears that endogenous testosterone inhibits wound healing and promotes inflammation since castration of male mice or systemic treatment with the androgen receptor antagonist flutamide accelerates cutaneous wound healing and reduces the inflammatory response. The aim of this review is to summarise our current knowledge about the regulation of tissue repair processes by androgens.
Keywords: Testosterone; androgen receptor; wound; castration; inflammation